Provitamin A-biofortified maize consumption increases serum xanthophylls and 13C-natural abundance of retinol in Zambian children - Sheftel, Jesse; Gannon, B. M.; Davis, CR; Tanumihardjo, S. A. (Frontiers Media, 2017)
Plants that undergo C4 photosynthesis, such as maize, are enriched in the stable isotope of carbon (13C) compared with other dietary plants and foods. Consumption of maize that has been biofortified to contain elevated levels of provitamin A carotenoids (orange maize) increased the abundance of 13C in serum retinol of Mongolian gerbils. We evaluated this method in humans to determine if it has potential for further use in intervention effectiveness studies. A random subset of samples from a two-month randomized controlled feeding trial of rural three- to five-year old Zambian children were used to determine the impact of orange maize intake on serum carotenoid concentrations ( n = 88) and 13C-natural abundance in serum retinol ( n = 77). Concentrations of β-cryptoxanthin (a xanthophyll provitamin A carotenoid) and the dihydroxy xanthophylls lutein and zeaxanthin, which do not have vitamin A activity, were elevated in children consuming orange maize compared with those consuming a white maize control ( P < 0.001), while β-carotene was not different ( P > 0.3). Furthermore, 13C natural abundance was higher after two months’ intervention in the orange maize group compared with the white maize group ( P = 0.049). Predictions made from equations developed in the aforementioned gerbil study estimated that maize provided 11% (2–21%, 95% confidence interval) of the recent dietary vitamin A to these children. These results demonstrate that orange maize is efficacious at providing retinol to the vitamin A pool in children through provitamin A carotenoids, as monitored by the change in 13C enrichment, which was not reflected in serum β-carotene concentrations. Further effectiveness studies in countries who have adopted orange maize should consider determining differences in retinol 13C-enrichment among target groups in addition to profiling serum xanthophyll carotenoids with specific emphasis on zeaxanthin.Maize biofortified with provitamin A carotenoids (orange) has been released in some African markets. Responsive and sensitive methods to evaluate dissemination effectiveness are needed. This study investigated methods to evaluate effectiveness of orange maize consumption using serum from Zambian children fed orange maize for two months. Many varieties of orange maize contain higher amounts of the xanthophyll carotenoids in addition to β-carotene compared with typical varieties. This study uniquely showed higher concentrations of the maize xanthophylls lutein, zeaxanthin, and β-cryptoxanthin in children who consumed orange maize compared with white. Furthermore, maize is a C4 plant and is therefore naturally enriched with 13C. Higher 13C was detected in the serum retinol of the orange maize consumers with no change in serum β-carotene concentration suggesting preferential bioconversion to retinol. The combined analyses of serum zeaxanthin specifically and 13C-natural abundance of retinol could prove useful in effectiveness studies between orange maize adopters and non-adopters.